The Third T(h)est - De Nooijer, Paul; Musser, King Jerry (The Netherlands; Filmmuseum, 1981)
Four people stand and sit in a row in a room. A fifth person walks through the space, and takes Polaroid pictures. After a while, he joins the row.
No Dialogue
Verzio Film Festival Submission
Keywords: Experimental films